Diagnostic yield of a novel tracer 68Ga-citrate in sarcoidosis patients: 68Ga-citrate PET/CT in sarcoidosis - Tetikkurt, Cuneyt; Kubat, Bahar; Sayman, Haluk Burcak; Yanardag, Halil; Bilir, Muammer (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
AbstractBackground: Sarcoidosis is a granulomatous disease of unknown origin. Conventional laboratory and imaging modalities may lead to equivocal conclusions for sarcoidosis diagnosis. 68Ga-citrate PET/CT has been utilized in the diagnosis of inflammatory and infectious diseases due to its beter  performance. Aims: This study was designed to determine the clinical trenchancy of 68Ga-citrate in sarcoidosis patients as an alternative tracer that binds to the somtastotin receptors of the inflammatory cells in sarcoid granulomas because current laboratory modalities may occasionally lack accuracy for sarcoidosis diagnosis. Conventional criteria including clinical, laboratory, radiologic modalities, and 18F-FDG PET/CT were compared with the 68Ga-citrate PET/CT to evaluate the diagnostic yield in sarcoidosis.Methods: Forty-four sarcoidosis patients were include in the study. Conventional laboratory and imaging  modalities were done in 44 while  68Ga-citrate PET/CT and 18F-FDG-PET/CT  were    performed in 22 patients. The three modalities were compared with in regard to granulomatous activity evaluation, extrapulmonary organ involvement, and identification of coexistent malignant disease.Results: 68Ga-citrate PET/CT revealed a significantly higher diagnostic yield for sarcoidosis compared to conventional laboratory and 18F-FDG-PET/CT imaging modalties. 68Ga-citrate PET/CT revealed 72.7% sensitivity and 68.4% specificity for the detection of granulomatous inflammation in sarcoidosis.Conclusions: 68Ga-citrate PET/CT was conclusive for activity assessment in sarcoidosis for diagnosis, activity assessment, and identification of extrapulmonary organ involvement. As an innovative novel tracer, 68Ga-citrate identified disease activity, extrapulmonary organ involvement, biopsy sites, and coexistent malignancy due to its chemical properties with a higher statistical diagnostic yield compared to conventional laboratory findings and the  PET/CT imaging manifestations in sarcoidosis.